The Influence of Financial, Service, Operations and Human Resources Aspects on Company Performance Using the Balanced Scorecard Method at PT. Adhya Tirta Batam - Hendrik Gomar Sinaga (SEAN Institute, 2024)
The Directorate General of Human Settlements, Ministry of PUPR who took over the function of the Drinking Water Supply System Development Support Agency (BPPSPAM) as a regulator or organizer of the Drinking Water Supply System (SPAM) throughout the territory of the Republic of Indonesia has implemented the Balanced Scorecard as a Performance Measurement Tool covering Financial, Service, Operations and Human Resources aspects of all PDAMs and other private drinking water companies that obtained concessions from the Government to meet the requirements of quality, quantity and continuity of drinking water supply system services to the community. The object of research is at PT Adhya Tirta Batam (ATB), the data studied is secondary data from financial statements. The data is analyzed by multiple regression analysis using the SPSS program. As a result, the research proves that all independent variables together have a significant effect on variable Y. The simultaneous test results show that the sig column. 0.000 < 0.005 level of significant (a). Partial test results show that the aspects of finance, service, operations and human resources partially have a significant effect on company performance, with sig. 0.000 < t table 0.05. The Adjusted R Square result obtained in this study is 0.895, which means that the ability of financial, service, operation and HR variables to explain the effect of company performance results is 89.5%, while the remaining 10.5% can be explained by other variables outside of this study.